Effect of Product Quality, Service Quality, and Safety Covid-19 Practice on Customer Satisfaction (Study on Rimbun Espresso & Brew Bar Padang) - Nina Firdausi; Syafrizal Syafrizal (Institute of Computer Science (IOCS), 2021)
This study aims to analyze the effect of product quality, service quality, and safety covid-19 practice on customer satisfaction. This is explanatory research using a quantitative approach with an instrument in the form of a questionnaire. The total population of this study was 202 respondents by using purposive sampling method. This study used SmartPLS to analyze the data. It was found that product quality, service quality, and safety covid-19 practice have a positive and significant effect on customer satisfaction.